PERGESERAN MATA PENCAHARIAN DAN PUDARNYA RITUAL SYUKUR LAUT PADA MASYARAKAT NELAYAN BUGIS DI SUNGAILIAT BANGKA - Dandung Budi Yuwono (Balai Penelitian dan Pengembangan Agama Makassar, 2019)
The Bugis fishing community in Sungailiat, Bangka as a religious ethnic representation of Islam is one group of fishermen who still live in poverty. The source of this paper is obtained from research that uses qualitative anthropological methods, aimed at seeing how religious practices, and how life strategies in sustaining their lives. The data collection applies techniques of observation and deep interview, whereas the data is analysed interpretively by appllying techniques of triangular analysis together with emic and ethical perspectives. The research findings show, the difficulty of meeting the needs of life, causing some fishermen to turn their livelihoods into tin mining pawners. The lack of intensity of the lives of fishermen in conducting fishing activities, coupled with the harsh accusations of shirk of the Mappanretation discourse from Muslim puritans and rationalist Muslim communities outside the fishing community, naturally dampens the ongoing Mappanretation ritual. As a result, the Mappanretation ritual as an expression of diversity gradually faded and eventually collapsed, disappeared, is no longer a tradition as long as it takes place in the life of the Bugis fishing community in Sungailiat.